Avaliação das propriedades mecânicas de geomateriais submetidos à percolação de lixiviados ácidos - Comparin, Isadora (2014)
Wastewater from industrial wastes and mining are an important source of environmental impact, due to their acidic constitution. In many cases, however, the disposal of such waste is inadequate, without any use of engineering techniques that provide appropriate containment such as compacted barriers in solid waste landfill sites. Although many studies in the literature have addressed the behavior of compacted barriers when subjected to the action of several types of contaminants, a few have explored the structural variations of the component materials of the barriers and the resulting changes in their physical and mechanical properties along the contaminant percolation and/or diffusion. In this context, the present work aims to evaluate the effects of acidic percolation on the mechanical degradation of geomaterials, with emphasis on changes in stiffness and strength. The reaserch program comprised two distinct stages: (1) the development and validation of a device for continuous measurement of stiffness in specimens subjected to acidic percolation, by using a non-destructive technique known as bender elements; and (2) a testing program to evaluation of tensile strength and the variations in hydraulic conductivity in specimens of a compacted clayey soil molded at different specific gravities, with and without the addition of Portland cement (1 and 2%), as they were subjected to the percolation of distilled water and/or sulfuric acid (2% volume concentration) in medium duration percolation tests. The validation tests for the stiffnessmeasuring device, carried out on specimens of an uniform cemented sand, showed consistent results in terms of the magnitudes of the deformation moduli obtained and the variations of these moduli with curing time. For the tests carried out on the compacted clayey soil, it was observed a remarkable reduction in the hydraulic conductivity with acid leaching. However, a strength degradation was not detected. Instead, for all specific gravities and cement contents investigated, it was noticed an increase in tensile strength after the specimens were subjected to acid leaching, which might be attributed to a reduction in voids ratio and to the evidence that cementation was not largely degraded by the acidic solution